AB0138 Interferon-gamma challenge of PBMC from patients with lupus nephritis in remission decreases suppressor of cytokine signaling 1 (SOCS1) and regulatory t cells (TREGS) and promotes immune activation. (15th June 2017) - Gibor, G; Arad, U; Wallman, J; Ablin, J; Aloush, V; Kaufman, I; Jacky, S; Caspi, D; Elkayam, O; Paran, D; Sharabi, A
Abstract : Background: Interferon-gamma (IFN-γ) plays an important role in the development of lupus nephritis (LN). Regulation of IFN-γ signaling that occurs in disease remission and in active LN is herein addressed. Objectives: To study the impact of IFN-γ on PBMC obtained from patients with LN in remission as compared to active LN. Methods: Sixteen patients fulfilling the ACR classification criteria for systemic lupus erythematosus were recruited. All patients had a history of LN of whom 10 were in remission (as defined by EULAR criteria) and 6 had active LN (as defined by SLEDAI-2K or BILAG). Healthy subjects (n=10) were included as a control group. Sera and PBMC were obtained from each individual. Flow cytometry, western blots and real time RT-PCR were used in processing and detection of cell subtypes, protein and mRNA levels. Recombinant human IFN-γ (rhIFN-γ) and anti-IFN-γ neutralizing antibody were used in vitro. Mann-Whitney and student t-tests were used for statistical analysis. Results: In active LN there was a significant 2-fold increase in CD4 + CD69 + activated T cells as compared to healthy subjects and patients in remission. Reactivity to interferon-gamma receptor was determined by the phosphorylation of its predominant transcription factor, signal transducer and activator of transcription 1 (STAT1) in the cells that were incubated with rhIFN-γ or with media alone. In active LN, 3- and 6-fold increase in pSTAT1 occurred with rhIFN-γ incubation during 24h and 48h, respectively, and healthy subjects responded likewise. In patients in remission, pSTAT1 increase was even higher (by 8- and 10-fold at 24h and 48h, respectively). After 24h incubation with rhIFN-g all groups had elevated (mRNA) expression of SOCS1, but at 48h, it significantly decreased in healthy subjects and in patients in remission by 34% and 50%, respectively. Further, at 24h the frequency of CD4 + CD127 low FoxP3 + regulatory T cells (e.g. Tregs) increased by 27–30% in active LN and in healthy subjects, and in remission it was minimally changed. At 48h, the frequency of Tregs significantly decreased in healthy subjects (to baseline levels before rhIFN-γ challenge) and in patients in remission (by 24%, p=0.003). A challenge of PBMC from LN patients in remission with sera (at 1% concentration) derived from patients with active LN resulted in 7.5-fold increase in pSTAT1 expression and 20–30% decrease in Tregs, however, combination of sera and anti-IFN-g neutralizing antibody resulted in 5-fold decrease in pSTAT1 expression and significantly diminished the decrease in Tregs. Conclusions: In LN in remission a challenge with IFN-γ could lead to immune activation and a risk of flare-up, as it results in a decrease in both SOCS1 and Tregs and a robust STAT1 phosphorylation. In active LN, STAT1 phosphorylation is less diminishing, as both SOCS1 and Tregs are saturated, which could affect their suppressive effectiveness. Disclosure of Interest: None declared